Pengaruh Pembelajaran Berbasis Berpikir Kritis Terhadap Peningkatan Prestasi Belajar PAI Di SDIT Adzkia 1 Sukabumi - Najrul Jimatul Rizki; H. Mulyawan S. Nugraha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Islamic Religious Education is an integral part of the educational curriculum which aims to develop understanding, values, and ethics based on Islamic religious teachings. In an effort to improve learning achievement in this field, a critical thinking-based learning approach has become the focus of attention. This study examines the impact of critical thinking-based learning on learning achievement in Islamic education. This research method uses a quantitative approach in which the results show that the application of critical thinking-based learning significantly influences learning achievement in Islamic Religious education. This approach allows students to develop the ability to think analytically, evaluatively and reflectively towards religious teachings, thus helping them understand and internalize religious concepts more deeply. then the results of the reliability coefficient of the instrument Variable X = 0.903, instrument Variable Y = 0.853, it turns out that the Cronbach Alpha value is greater than r table with a significance of 5% = 0.367, which means that the instrument is stated to be reliable. The results of the data normality test with Shapiro Wilk's significance value were 0.624 and 0.315 greater than 0.05, so it can be concluded that the results of the residual values are normally distributed. The value of the correlation or relationship (R) is equal to 0.623. From this output, the coefficient of determination (R Square) is 0.388, which implies that the effect of the independent variable (critical thinking) on the commitment variable (learning achievement) is 38.8%.